Adequacy of posthypertonic shock model to real cryopreservation conditions during deglycerolization of erythrocytes - Чабаненко, О.О.; Єршова, Н.А.; Шпакова, Н.М. (The 57th annual meeting of the Society for Cryobiology «CRYO-2020» 21-23 July 2020, USA. Cryobiology.- V. 97.- P. 276, 2020)
The research was to compare the efficiency of amphiphilic compounds belonging to different classes of surface-active substances under conditions of posthypertonic shock of human erythrocytes and at the stage of glycerol removal from cryopreserved cells. We used anionic sodium decyl sulfate, cationic trifluoperazine and nonionic decyl-b,D-glucopyranoside. Posthypertonic shock was initiated by transferring erythrocytes from dehydration (1.65 mol/L NaCl) into rehydration medium (0.15 mol/L NaCl) at 37 and 0 C. Erythrocyte suspension was frozen with glycerol (15%) by immersion into liquid nitrogen. To remove glycerol from warmed cells we used 0.6 mol/L (once) and 0.15 mol/L (twice) NaCl solution. Amphiphilic compounds were added into rehydration medium upon posthypertonic shock of erythrocytes and into second wash solution (0.15 mol/L NaCl) during deglycerolization of warmed cells. All studied amphiphilic compounds, regardless of their physicochemical properties and, as a consequence, the character of different transmembrane distribution under conditions of posthypertonic shock of erythrocytes at 0 C, were established to show quite a high antihemolytic activity (60e70%). At 37 С no protective effect of amphiphiles was revealed. Application of amphiphiles in deglycerolization of warmed erythrocytes enabled to reduce the level of cells hemolysis by 2e5 times, the most effective was nonionic decyl-b,D-glucopyranoside, which antihemolytic activity was ~ 90%. The research findings on the efficiency of studied amphiphilic compounds using in a model and real conditions of glycerol removal from warmed cells suggest a unified mechanism of their action. As well we hypothesize that it can be used for improvement of erythrocytes quality.
Chabanenko O, Yershova N, Shpakova N. Adequacy of posthypertonic shock model to real cryopreservation conditions during deglycerolization of erythrocytes. In: The 57th annual meeting of the Society for Cryobiology «CRYO-2020». 21-23 July 2020, USA. Cryobiology. 2020; 97: 276
Keywords: амфіфільні речовини; еритроцити людини; постгіпертонічний шок; amphiphilic compounds; erythrocytes; posthypertonic shock